Fictional Remembrances of Sir Thomas More: Part I - The Sixteenth Century1. (June 2016) - Closel, Régis Augustus Bars
Abstract : This article focuses on how literary works such as plays in 16th–17th century England dealt with the fictional presence of Sir Thomas More. Among Tudor statesmen, Thomas More had a special appeal as a topic of thought during the Elizabethan–Jacobean period, quite apart from his opposition to the marriage which led to the reign of Queen Elizabeth. The Marian, Elizabethan and Jacobean periods cover the range of the selected works. They compose a heterogeneous and intriguing group in which every piece has its own particular way of remembering Thomas More. Six works are presented here: the dialogue Il Moro (1556), by Ellis Heywood; a late morality play, The Longer Thou Livest the More Fool Thou Art (1569), by William Wager; a novel, The Unfortunate Traveller (1594), by Thomas Nashe; and three plays, Cromwell (1602), by an unknown dramatist, Sir Thomas More (1600–1603/4), by five different dramatists, and Henry VIII (1613), by William Shakespeare and John Fletcher. Due to the scope of this research, the article is written in two parts. This part explores the first three sixteenth century fictional works by Wager, Heywood and Nashe.